Assessing the Long-Term and Short-Term Influences on Trade Value in Indonesia: Evidence from Economic, Industrial, and Monetary Factors - Basuki, Agus Tri (Balance : Jurnal Akuntansi dan Manajemen, 2024)
This study aims to analyse the impact of economic growth, inflation, exchange rates, industrial added value, and investment on Indonesia's trade value in the period 1989-2022. The data used were sourced from the World Development Indicators and analysed using the Error Correction Model (ECM) approach. The results of the study show that economic growth has a negative influence on the value of trade, both in the short and long term. On the other hand, inflation, the rupiah exchange rate against the dollar, industrial value-added, and investment have a positive influence on trade value, both in the short and long term. Based on these findings, policies that can be taken to increase Indonesia's trade value include: first, more stable economic policies to reduce the negative impact of economic growth on trade; second, monetary policy that can control inflation and maintain the stability of the rupiah exchange rate against the dollar; third, strengthening the industrial sector by encouraging investment and increasing industrial added value to increase export competitiveness; and fourth, policies that support a better investment climate to attract sustainable domestic and foreign investment. This research provides important insights for policymakers in formulating economic strategies that can support the increase in the value of Indonesia's trade in the global market.